PENETAPAN STANDARISASI PENGOLAHAN ARAK DESA BESAN BERBASIS KEARIFAN LOKAL - Ni Wayan Widhiasthini; Nyoman Sri Subawa; Putu Ayu Titha Paramita Pika (LP2M STP Mataram, 2022)
Purpose: the purpose of this description of community service is to help the community in systematically compiling SOPs. Research methodology: Observing the field and formulating the flow of the preparation mechanism according to the conditions that occur. Results: Standard Operating Procedure is a document related to procedures carried out chronologically to complete a job with the aim of obtaining effective, efficient, and constant quality work. In its application, there are still many home industries that have not implemented a standardization system so that the products produced still have suboptimal quality, including the Balinese Arak produced by Besan Village. This can have an impact on consumer confidence in the product. To overcome this problem, real steps are needed in the form of preparing SOPs, without eliminating the content of local wisdom in the traditional production process and the purity of the resulting arak. Through the breakthroughs made, arak, which has legalized its existence in Bali, can be widely marketed and become a source of driving the creative economy of the community. Limitations: Limitations in this activity, wider community involvement so as to produce SOPs that can be generally accepted for craftsmen. Contribution: A description in formulating SOPs to contribute to society in production and the mechanisms that must be carried out so as to produce quality products.